Accurate Determination of the Minimum HOMO Offset for Efficient Charge Generation using Organic Semiconducting Alloys. Issue 5 (16th December 2019) - Zhang, Jianyun; Liu, Wenrui; Zhou, Guanqing; Yi, Yuanping; Xu, Shengjie; Liu, Feng; Zhu, Haiming; Zhu, Xiaozhang
Abstract: Current research indicates that exciton dissociation into free charge carriers can be achieved in material combinations with the highest occupied molecular orbital (HOMO) offset lowered to 0 eV in non‐fullerene organic solar cells. However, the quantitative relationship between the HOMO offset and exciton dissociation has not been established because of the difficulty in achieving continuously tunable HOMO offsets. Here, the binary blends of PTQ10:ZITI‐S and PTQ10:ZITI‐N are combined to form the positive and negative HOMO offsets of 0.20 and −0.07 eV, respectively. While the PTQ10:ZITI‐S binary blend delivers a decent power conversion efficiency (PCE) of 10.69% with a short‐circuit current ( J sc ) of 16.94 mA cm −2, the PTQ10:ZITI‐N with the negative offset shows a much lower PCE of 7.06% mainly because of the low J sc of 12.03 mA cm −2 . Because the tunable HOMO levels can be realized in organic semiconducting alloys based on ZITI‐N and ZITI‐S acceptors, the transformation of the HOMO energy offset from negative to positive values is achieved in the PTQ10:ZITIN:ZITI‐S ternary blends, delivering much‐improved PCEs up to 13.26% with a significant, 74% enhancement of J sc to 20.93 mA cm −2 . With detailed investigations, the study reveals that the minimum HOMO offset of ≈40 meV is required to achieve the most‐efficient exciton dissociation and photovoltaic performance. Abstract : Exciton dissociation into free charges is the most important optoelectronic process in organic solar cells, which is driven by the energy‐level offset of electron‐donor and ‐acceptor materials. With the continuously tunable HOMO level achieved by organic semiconducting alloys, the minimum HOMO offset of ≈40 meV is shown to be necessary to achieve the most efficient exciton dissociation and photovoltaic performance.